Childrens’ socio-religious and personal development through the lens of teacher at early childhood education in Pakistan - Ali, Muhammad Qasim; Saleh, Salmiza (Southeast Asia Early Childhood Journal, 2022)
Early childhood period indicates the drastic changes in an individual's social and personal development. Teachers devise different pedagogical practice to enhance students' social and personal development at early childhood education. The objective of the study is to explore students' socio-religious and personal development at Early Childhood Education (ECE) in Pakistan. Researchers used qualitative method and case study research used for the study. The researchers chose 20 primary schools in the Pakpattan district with ECE rooms and one trained primary school teacher from each school. In interviews and observations, themes are identified. Then they interpret and describe the recoded observation sheet to meet the study's objectives. The study concluded that the students in the ECE room where they make the fullest use of greetings according to the situation show their socio-religious and extrovert nature. The study also concluded that students have developed their listening skills that are part of their personal development, whereas it also concluded that students are conscious about cleanliness that is an integral part of Islamic teachings. The study concluded that the students in the ECE room where they make the fullest use of greetings according to the situation show their socio-religious and extrovert nature. The study also concluded that students have developed their listening skills that are part of their personal development, whereas it also concluded that students are conscious about cleanliness that is an integral part of Islamic teachings. The study's pedagogical implications suggest that early childhood educators should be taught new methods to address current socio-religious requirements and that ECE classrooms should be outfitted with modern technology to facilitate better and foster student learning.